Programmed necrotic cell death of macrophages: Focus on pyroptosis, necroptosis, and parthanatos - Nirmal Robinson; Raja Ganesan; Csaba Hegedűs; Katalin Kovács; Thomas A. Kufer; László Virág (2019)
Macrophages are highly plastic cells of the innate immune system. Macrophages play central roles in immunity against microbes and contribute to a wide array of pathologies. The processes of macrophage activation and their functions have attracted considerable attention from life scientists. Although macrophages are highly resistant to many toxic stimuli, including oxidative stress, macrophage death has been reported in certain diseases, such as viral infections, tuberculosis, atherosclerotic plaque development, inflammation, and sepsis. While most studies on macrophage death focused on apoptosis, a significant body of data indicates that programmed necrotic cell death forms may be equally important modes of macrophage death. Three such regulated necrotic cell death modalities in macrophages contribute to different pathologies, including necroptosis, pyroptosis, and parthanatos. Various reactive oxygen and nitrogen species, such as superoxide, hydrogen peroxide, and peroxynitrite have been shown to act as triggers, mediators, or modulators in regulated necrotic cell death pathways. Here we discuss recent advances in necroptosis, pyroptosis, and parthanatos, with a strong focus on the role of redox homeostasis in the regulation of these events.